Integrasi Pendekatan Tekstual dan Kontekstual terhadap Hadis Sahih di Era Modern - Syauky, Ahmad; Nurmila, Nurmila; Ariani, Safrina (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2025)
Understanding ṣaḥīḥ ḥadīths has remained a critical methodological discourse in both classical and contemporary Islamic studies. Two major hermeneutical approaches—textual and contextual—are central to this discourse. The textual approach emphasizes a literalist reading of the ḥadīth text in order to preserve the authenticity and sanctity of the Prophet Muhammad’s teachings. In contrast, the contextual approach considers the socio-historical and cultural background in which a ḥadīth was transmitted, thereby enabling its normative messages to remain relevant to contemporary realities. This article addresses the methodological question of how these two interpretative approaches can be integrated to respond to the dynamic challenges of modern Muslim life.This study employs a qualitative-descriptive method using a library research model. The primary sources include both classical ḥadīth compilations and contemporary scholarly literature. Selected ṣaḥīḥ ḥadīths that are often debated between textualist and contextualist interpretations are analyzed to demonstrate the theoretical implications of both approaches. Findings indicate that the textual and contextual approaches are not inherently contradictory but rather complementary. The textual method safeguards the transmissional integrity (riwāyah) of the ḥadīth, while the contextual approach ensures that its meanings (dirāyah) can be appropriately situated within evolving socio-cultural frameworks. The integration of both provides a more balanced and comprehensive understanding of Prophetic traditions. In conclusion, a synthesis between textual fidelity and contextual relevance is essential to interpret ḥadīths holistically. This integrative framework is proposed as a viable model for contemporary ḥadīth interpretation that is both normatively authentic and socially responsive.